The effect of antidiabetic activity of eurycoma longifolia, orthosiphon stamineus and punica granatum combined extracts on streptozotocin-induced diabetic rats - Osama Abdulmunem, Khayri Al-Obaidi (2020)
Diabetes mellitus (DM) is a metabolic syndrome that is currently being managed using different brands of prescribed medications; however, these medications are associated with different side effects. As such, medical plants are considered an alternative in traditional medicines for treating DM as they have no side effects. The present study was conceived with the aim of studying generally medicinal plants extracts in terms of their